Kontribusi Dukungan Sosial dan Intensitas Penggunaan Media Sosial terhadap Kesehatan Mental Gen Z - Achmad, Rifki (YASIN, 2024)
This study was conducted to determine how social support and intensity of social media use contribute to Gen Z's mental health. The research method used was a quantitative approach with a correlational type. The research sample was taken using purposive sampling technique with the criteria of Gen Z students, aged 20-22 years and actively using social media on average more than 3 hours a day. Gen Z who participated as research subjects amounted to 100 people. The instruments used in this study were the social support scale, SONTUS to measure the intensity of social media use, and GHQ-12 for mental health, all of which were structured using the Likert model. The data analysis technique used was multiple linear regression analysis. The results showed that social support and intensity of social media use contributed to mental health by 17.5%. So that the higher the social support and intensity of social media use, the higher Gen Z's mental health will be.